Water the roots.
Edna Manley College of the Visual and Performing Arts presents Water the roots to be held on Saturday October 17, 2015 at 8 p.m. at The Bridge, Edna Manley College of the Visual and Performing Arts Arthur Wint Drive. MCs: Donald "Iceman" Anderson and Simone "Chuka" Simpson; park-shuttle service/park and ride available at the National Stadium.
Posters are located in drawer #1.
Keywords: Arts -- Music -- Jamaica; Posters -- Jamaica